Mendalami Dampak Perselisihan Orang Tua terhadap Kecerdasan Emosional Anak di Keluarga Kristiani - Manurung, Kosma (Sekolah Tinggi Agama Kristen Samarinda, 2024)
Abstract: Family harmony is the dream of every human being who builds a household ark. Unfortunately, sometimes the reality in the family presents different facts. Instead of harmony, what happens is that the dispute between the two parents is shown in front of their children. Every incident of dispute that is seen by children, must be left in their memory. In addition, this leaves scars on his heart which impact his emotional intelligence as well. This research seeks to explore the impact of parental disputes on the emotional intelligence of children in Christian families. It is hoped that the use of a narrative qualitative method that is strengthened by literature review is expected to be able to provide a strong, careful, and systematic description of the biblical narrative about parental disputes, children's emotional intelligence, and the impact of parental disputes on children's emotional intelligence in Christian families. It was concluded that parental disputes in Christian families had an impact on children's irritable behavior, lack of self-confidence, children's difficulties with empathy, and children experiencing moral degradation. Abstrak: Keharmonisan keluarga adalah dambaan setiap insan yang membangun bahtera rumah tangga. Sayangnya kadang kenyataan di keluarga memaparkan fakta yang berbeda, bukannya keharmonisan malah yang terjadi justru perselisihan kedua orang tua yang dipertontonkan di hadapan anak-anaknya. Setiap peristiwa perselisihan yang dilihat oleh anak, pasti membekas dalam ingat mereka. Selain itu, hal ini meninggalkan luka pada hatinya yang berdampak juga pada kecerdasan emosionalnya. Penelitian ini berupaya mendalami dampak perselisihan orang tua terhadap kecerdasan emosional anak di keluarga Kristiani. Penggunaan metode kualitatif naratif yang diperkokoh kajian literatur diharapkan mampu memberikan gambaran yang kuat, cermat, serta sistimatik terkait narasi Alkitab tentang perselisihan orang tua, kecerdasan emosional anak, dan dampak perselisihan orang tua terhadap kecerdasan emosional anak di keluarga Kristiani. Disimpulkan bahwa perselisihan orang tua di keluarga Kristiani berdampak pada perilaku anak yang mudah marah, kurangnya kepercayaan diri anak, kesulitan anak berempati, dan anak mengalami degradasi moral.